STING couples with PI3K to regulate actin reorganization during BCR activation - Jing YK; Dai X; Yang L; Kang DQ; Jiang PP; Li N; Cheng JL; Li JW; Miller H; Ren BX; Gong Q; Yin W; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2022)
The adaptor protein, STING (stimulator of interferon genes), has been rarely studied in adaptive immunity. We used Sting KO mice and a patient's mutated STING cells to study the effect of STING deficiency on B cell development, differentiation, and BCR signaling. We found that STING deficiency promotes the differentiation of marginal zone B cells. STING is involved in BCR activation and negatively regulates the activation of CD1 9 and Btk but positively regulates the activation of SHIP. The activation of WASP and accumulation of F-actin were enhanced in Sting KO B cells upon BCR stimulation. Mechanistically, STING uses PI3K mediated by the CD19-Btk axis as a central hub for controlling the actin remodeling that, in turn, offers feedback to BCR signaling. Overall, our study provides a mechanism of how STING regulates BCR signaling via feedback from actin reorganization, which contributes to positive regulation of STING on the humoral immune response.